2023
DOI: 10.3390/tropicalmed8020082
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infection with SARS-CoV-2 and Orientia tsutsugamushi during the COVID-19 Pandemic in the Maldives

Abstract: The COVID-19 pandemic was the worst public-health crisis in recent history. The impact of the pandemic in tropical regions was further complicated by other endemic tropical diseases, which can cause concurrent infections along with COVID-19. Here, we describe the clinical course of a patient with concurrent COVID-19 and scrub typhus infection. The patient’s de-identified clinical data were retrieved retrospectively. The patient had progressive breathlessness at the time of presentation and was hospitalized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Scrub typhus presents diagnostic challenges, as it closely resembles other febrile illnesses such as dengue, typhoid fever, leptospirosis, murine typhus and corona virus [8,90].The presence of an eschar in patients can aid in the clinical diagnosis of scrub typhus with higher specificity, but it often goes unnoticed as it is non-itching, painless, and typically present in areas like the perineum, groin, and axilla [91]. Available studies reported the prevalence of eschar and rash ranging from 7% to 28.8% and 1.69% to 28%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Scrub typhus presents diagnostic challenges, as it closely resembles other febrile illnesses such as dengue, typhoid fever, leptospirosis, murine typhus and corona virus [8,90].The presence of an eschar in patients can aid in the clinical diagnosis of scrub typhus with higher specificity, but it often goes unnoticed as it is non-itching, painless, and typically present in areas like the perineum, groin, and axilla [91]. Available studies reported the prevalence of eschar and rash ranging from 7% to 28.8% and 1.69% to 28%, respectively.…”
Section: Discussionmentioning
confidence: 99%